Social demand functions in general equilibrium - Yves Balasko (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
Social demand functions result from the budget constrained maximization of “social preferences” or “other regarding preferences.” These preferences are non-selfishin the sense that they also depend on other consumers' wealth. This paper addresse sthe robustness to wealth externalities of the classical general equilibrium model with finite numbers of goods and consumers. The existence of equilibrium, the genericity of regular economies and, at those regular economies, the finite odd number of equilibria and the local continuity of equilibrium selection maps, and finally the identification (or diffeomorphism) of the equilibrium manifold with a Euclidean space are shown to be satisfied independently of the size of those wealth externalities provided total resources are variable
Keywords: C62; D11; D50; D51; 330; social preferences; wealth externalities; general equilibrium; demand functions